Serum Creatinine Reference Limits in Pediatric Population—A Single Center Electronic Health Record-Based Database in Taiwan - Chuang, Gwo-Tsann; Tsai, I-Jung; Tsau, Yong-Kwei (Frontiers in Pediatrics, 2021)
Objective To assess the age- and gender-specific normal serum creatinine level in Taiwan pediatric population. Study design Serum creatinine levels were retrieved via National Taiwan University Hospital-integrated Medical Database. Due to the possibility of having acute kidney injury or chronic kidney disease, individuals with multiple serum creatinine measurements were excluded, and outliers in each age- and gender-specific group were also removed subsequently. The remaining creatinine levels in each group were assessed and 95% reference intervals were established. Results After the exclusion steps, 27,911 remained with a single corresponding serum creatinine data. Reference for each age- and gender-specific group creatinine level were generated. The upper reference limits (URLs), which were particularly useful for clinical use, followed the natural increasing trend of serum creatinine with age. Conclusion We generated the serum creatinine URLs from a single hospital-integrated medical database in Taiwan for different age and gender in pediatric population. The results will aid physicians in clinical practice regarding to renal function evaluation, especially for patients without a recent baseline serum creatinine level.